Relationship Between Percutaneous Transhepatic Cholangioscopy Findings and Pattern of Carcinomatous Spread in the Bile Duct. Issue 1 (1994) - Sato, M.; Maetani, I.; Ohashi, S.; Ogawa, S.; Anzai, T.; Hoshi, H.; Yoshioka, H.; Igarashi, Y.; Sakai, Y.
Abstract : To clarify the relationship between percutaneous transhepatic cholangioscopic findings such as papillogranular surface and vascular dilation, which are reportedly characteristic of carcinoma, and the pattern of spread for bile duct carcinomas, we compared endoscopic photographs with histological features of biopsy specimens in 57 regions of specimens from 35 patients with malignant stenosis of the bile duct. Regions with a papillogranular surface were associated with noninvasive mucosal carcinomas and papillary proliferation of superficial epithelia significantly more often than regions without such a surface (P<0.0001). The sensitivity and specificity of the papillogranular surface to noninvasive mucosal carcinoma was 79 and 95%, respectively, that of papillary proliferation of superficial epithelia was 100 and 98%, respectively. Regions with vascular dilation were associated with invasive carcinoma significantly more often than regions without vascular dilation (P<0.0001). The sensitivity and specificity of vascular dilation to invasive carcinoma were 90 and 86%, respectively. Results indicate that a papillogranular surface is related to noninvasive mucosal carcinomas while vascular dilation is related to invasive carcinomas. However, a papillogranular surface was even more closely related to papillary proliferation of superficial epithelia.